Role of Melatonin in Reducing Post-Operative Delirium in Coronary Artery Bypass Graft Surgery - Rehmani, Syed Jawad; Shah, Syed Aqeel Hussain; Khan, Umer; Khan, Tanveer Ahmed; Abid, Komail; Memon, Muhammad Ali (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the role of melatonin in the reduction of postoperative delirium in On pump Coronary artery bypass graft (CABG) patients.Study Design: Quasi experimental study.Place and Duration of Study: Department of Cardiac Anesthesia and Intensive Care Department, Armed Forces Institute of Cardiology and National Institute of Heart Diseases, Rawalpindi Pakistan, from Oct -Dec 2023.Methodology: Two hundred ten patients, irrespective of gender, between the ages of 30 and 60 years, who undergone On pump CABG, were recruited. Non-randomly, the patients were divided into two groups: the Experimental-Group (received melatonin) and the Control-Group (did not receive melatonin). Impact of Melatonin on Delirium was assessed by Confusion Assessment Method for Intensive care Unit (CAM-ICU) and outcomes were compared with standard treatment Control-GroupResults: Among 210 patients, 179(85.2%) were male and 31(14.8%) were female. Occurrence of delirium after 24 hours post-operative CABG surgery in group receiving melatonin was 21(20.6%) whereas 47(43.5%) in control group which was clinically significant (p